One step synthesis of quantum dot-magnetic nanoparticle heterodimers for dual modal imaging applications - Lee, Jiyeon; Hwang, Gyoyeon; Hong, Yeon Sun; Sim, Taebo (Royal Society of Chemistry, 2015)
Dual modal nanoprobes are promising tools for accurately detecting target molecules as part of the diagnosis of diseases including cancers. We have explored a new dual modal bioimaging probe that is comprised of a quantum dot (QD)-magnetic nanoparticle (MNP) hybrid. The MNP-QD heterodimers explored are fabricated by using a platinum-guanine coordination bonding guided self-assembly process, employing the metal-DNA conjugation method. Investigations utilizing energy dispersive spectroscopy (EDS) equipped high resolution transmission electron microscopy (HRTEM) demonstrate that the heterodimer contains an iron (Fe) dominant MNP and a cadmium (Cd) dominant QD. Finally, the results of cell studies show that the MNP-QD conjugates display good HeLa cell uptake in the absence of non-specific binding to the cell membrane and, as such, they can be used to label cells in vitro and in vivo as part of a new cell imaging technique.
Keywords: DELIVERY; PROBES; SYSTEM; OXIDE